Procedures and toolsused in the investigationof New Zealand's historical earthquakes - G. L. Downes (Annals of Geophysics, 2004)
New Zealand?s tectonic setting, astride an obliquely convergent tectonic boundary, means that it has experienced many large earthquakes in its 200-year written historical records. The task of identifying and studying the largest early instrumental and pre-instrumental earthquakes, as well as identifying the smaller events, is being actively pursued in order to reduce gaps in knowledge and to ensure as complete and comprehensive a catalogue as is possible. The task of quantifying historical earthquake locations and magnitudes is made difficult by several factors. These include the range of possible earthquake focal depths, and the sparse, temporally- and spatially-variable historical population distribution which affects the availability of felt intensity information, and hence, the completeness levels of the catalogue. This paper overviews the procedures and tools used in the analysis, parameterisation, and recording of historical New Zealand earthquakes, with examples from recently studied historical events. In particular, the 1855 M 8+ Wairarapa earthquake is discussed, as well as its importance for the eminent 19th century British geologist, Sir Charles Lyell, and for future global understanding of the connection between large earthquakes and sudden uplift, tilting and faulting on a regional scale.